SURVIVAL OF YOUNG TILAPIA MOSSAMBICA PETERS AT DIFFERENT SALINITIES - Kader, A; Zafar, D; Bhuiyan, A L (Indian Journal of Fisheries, 2011)
Experiments were conducted first with the monacclimatized and then with the acclimatized fishes. In each aquarium, 5 young unacclimatized T. mossambica were released. After 24 h 0.5 g of rice ’bran was supplied to each aquarium. The unused1 food and excreta settled at the bottom of the aquaria were siphoned out at the end of every 24 h.